Superficial swab versus deep-tissue biopsy for the microbiological diagnosis of local infection in advanced-stage pressure ulcers of spinal-cord-injured patients: a prospective study. (December 2017) - Tedeschi, S.; Negosanti, L.; Sgarzani, R.; Trapani, F.; Pignanelli, S.; Battilana, M.; Capirossi, R.; Brillanti Ventura, D.; Giannella, M.; Bartoletti, M.; Tumietto, F.; Cristini, F.; et al.
Abstract: Objective: To assess the predictive value of superficial ulcer swab culture to make a microbiological diagnosis of deep wound infections in spinal cord injury (SCI) patients with advanced-stage pressure ulcers. Methods: From July 2011 to February 2014, we performed a prospective, single-centre study on adult SCI patients undergoing scheduled surgical debridement and reconstruction for advanced-stage pressure ulcers, at Montecatone Rehabilitation Institute, a 150-bed hospital dedicated to SCI care. Three superficial ulcer swabs were preoperatively collected using the Levine technique, then sent for culture. In surgery, multiple bone and soft-tissue specimens were taken and sent for culture and histological examination. No antibiotics were administered before surgery. The results of swabs and intraoperative specimens were compared. Results: In all, 116 patients were included, median age 49 years; a majority were males with post-traumatic paraplegia. According to intraoperative specimen cultures, the most common micro-organisms were Staphylococcus aureus, Proteus mirabilis, and Pseudomonas aeruginosa, found in 31, 27, and 16 cases, respectively. Concordance between superficial swabs and intraoperative specimen culture was found in only in 25 out of 116 cases (22%). The main reason for non-concordance was the yielding of different micro-organisms (41 out of 116); false negatives (swab negative/intraoperative positive) accounted for 31 out of 116 and false positives (swab positive/intraoperative negative) for 19 out of 116. When compared with intraoperative specimens, sensitivity and specificity of the swab culture were 80% and 54%, respectively. Conclusions: Our results confirm that in patients with advanced-stage pressure ulcers, the cultures of a superficial ulcer swab are not useful in either the diagnosis of a superinfection or the prediction of the role of involved micro-organisms.